Association study of detoxification genes in age related macular degeneration. Issue 4 (17th March 2005) - Esfandiary, H; Chakravarthy, U; Patterson, C; Young, I; Hughes, A E
Abstract : Background/aims: Age related macular degeneration (AMD) is a complex disorder leading to loss of central vision, and identification of risk factors associated with susceptibility to AMD has been a key objective for ophthalmic genetics research for almost a decade. This association study has examined genetic polymorphisms in 12 candidate genes as possible risk factors for predisposition to the development of the exudative variant of AMD in a Northern Irish population. The choice of genes was based on their function in the breakdown of industrial pollutants, cigarette smoke, defence against oxidative stress, or involvement in the general ageing process. Methods: Up to five single nucleotide polymorphisms (SNPs) were typed for CYP1A1, CYP1A2, CYP2E1, CYP2D6, EPHX1, MnSOD, AhR, NAT2, CAT, GPX1, PON1, and ADPRT1 by multiplex snapshot single base primer extension method. Genes showing high linkage disequilibrium (LD) between SNPs were analysed by haplotype analysis. Genes showing low LD were assessed using individual SNPs based on genotypes. Results: After correction for number of genes/SNPs tested, no significant association with AMD was found although several genes merit further investigation. This study suggests that a coding SNP in EPHX1 (Y113H) may be important in AMD and supports a previous observation of an association with exudative AMD. In addition, haplotype analysis highlighted ADPRT1, CYP2D6, and AhR as worthy of further study. Conclusion: This study has identified a number of genes requiring further investigation including EPHX1, ADPRT1, CYP2D6, and AhR.